White rot fungal impact on the evolution of simple phenols during decay of silver fir wood by UHPLC‐HQOMS. Issue 2 (28th July 2021) - Di Lella, Stefania; La Porta, Nicola; Tognetti, Roberto; Lombardi, Fabio; Nardin, Tiziana; Larcher, Roberto
Abstract: Introduction: Silver fir ( Abies alba Mill.) is one of the most valuable conifer wood species in Europe. Among the main opportunistic pathogens that cause root and butt rot on silver fir are Armillaria ostoyae and Heterobasidion abietinum . Due to the different enzymatic pools of these wood‐decay fungi, different strategies in metabolizing the phenols were available. Objective: This work explores the changes in phenolic compounds during silver fir wood degradation. Methodology: Phenols were analyzed before and after fungus inoculation in silver fir macerated wood after 2, 4 and 6 months. All samples were analyzed using high‐performance liquid chromatography coupled to a hybrid quadrupole‐orbitrap mass spectrometer. Results: Thirteen compounds, including simple phenols, alkylphenyl alcohols, hydroxybenzoketones, hydroxycinnamaldehydes, hydroxybenzaldehydes, hydroxyphenylacetic acids, hydroxycinnamic acids, hydroxybenzoic acids and hydroxycoumarins, were detected. Pyrocatechol, coniferyl alcohol, acetovanillone, vanillin, benzoic acid, 4‐hydroxybenzoic acid and vanillic acid contents decreased during the degradation process. Methyl vanillate, ferulic acid and p ‐coumaric were initially produced and then degraded. Scopoletin was accumulated. Pyrocatechol, acetovanillone and methyl vanillate were found for the first time in both degrading and non‐degrading wood of silver fir. Conclusions: Despite differences in the enzymatic pool, both fungi caused a significant decrease in the amounts of phenolic compounds with the accumulation of the only scopoletin. Principal component analysis revealed an initial differentiation between the degradation activity of the two fungal species during degradation, but similar phenolic contents at the end of wood degradation. Abstract : Phenols were evaluated during silver fir degradation after inoculation with fungi.